2014
DOI: 10.1161/circimaging.113.001177
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in Asymptomatic Aortic Regurgitation in the Era of Guidelines

Abstract: Background-The decision-making role of exercise echocardiography in the surgical timing for aortic regurgitation remains a matter of debate because of limited data on its link with outcome. The aim of this study was to assess the role of echocardiographic measurements at rest and during exercise as predictors of valve surgery in asymptomatic aortic regurgitation. Methods and Results-Comprehensive resting and exercise echocardiography was performed in 159 consecutive patients (50±15 years; 80% male) with isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 33 publications
3
44
2
3
Order By: Relevance
“…This suggests that more sensitive markers are required to detect subclinical RV dysfunction. Several investigators have suggested that RV strain can detect cardiac dysfunction earlier than standard imaging parameters and is associated with clinical outcomes(6,7,14).Our findings support the advantage of RV strain in the early detection of RV dysfunction. Therefore, the combination of impaired RV strain and increased SPAP may provide incremental predictive value for the prognosis of LTx patients.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that more sensitive markers are required to detect subclinical RV dysfunction. Several investigators have suggested that RV strain can detect cardiac dysfunction earlier than standard imaging parameters and is associated with clinical outcomes(6,7,14).Our findings support the advantage of RV strain in the early detection of RV dysfunction. Therefore, the combination of impaired RV strain and increased SPAP may provide incremental predictive value for the prognosis of LTx patients.…”
supporting
confidence: 85%
“…Therefore, the evaluation of PHT in the absence of knowledge of related cardiac changes, in particular RV function, may be problematic. Recent work has shown that direct measurement of RV function with strain imaging (RV strain) is related to outcome in valve disease and end-stage heart failure (5)(6)(7). In addition, successful LTx may lead to normalization of RV morphology and function, and the prognostic value of RV morphology and function before and after LTx has not been well characterized (8,9).…”
mentioning
confidence: 99%
“…The PA pressure, presence of dynamic MR and reversible ischaemia may also be assessed as potential contributors to symptoms. Assessment of RV function by TAPSE can be performed with exercise, and if <21 mm has been associated with the need for earlier aortic valve replacement45 GLS and tissue Doppler-derived mitral annular velocities have also been proposed in small studies,46 47 but not included in guidelines.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
“…Exercise tricuspid annular plane systolic excursion (TAPSE), a simple parameter used to assess RV function, which can easily be performed with exercise, was found to be independently associated with the need for earlier AVR in patients with asymptomatic severe AR if <21 mm [35]. Other recent research has proposed parameters such as exercise tissue Doppler peak systolic mitral annular velocity and atrioventricular plane displacement, as well as exercise global longitudinal function, which will require further evaluation prior to acceptance in clinical practice [36,37].…”
Section: Aortic Valvementioning
confidence: 99%